Intelligent Filling Method of Power Grid Working Ticket Based on Historical Ticket Knowledge Base - An, Zhiguo; Yi, Mancheng; Liu, Jing; Li, Ying; Peng, Zheng; Yu, Sifan; Liu, Jianxin; Huang, Weirong; Fang, Chunhua (Frontiers in Energy Research, 2021)
Traditional power grid ticket filling method has a large workload, low efficiency, and can not achieve comprehensive and effective reference of historical tickets. This paper proposes a method of intelligent filling in power grid working ticket based on historical ticket knowledge base. Firstly, the historical ticket data is preprocessed, then the historical ticket information is mined by association rule algorithm, and the method of establishing historical ticket knowledge base is proposed. Based on the improved word bag model, an intelligent grid work ticket filling model is established based on the historical ticket knowledge base, and the correctness of the method is verified by an example. The results show, the accuracy of the proposed method is at least 18 percentage points higher than that of the traditional model, and the matching efficiency is 1/2 higher than the evaluation results of the three models based on semantic expressions. The method enables the identification and extraction of similar and associated work tickets, improves the efficiency of filling work tickets for power grids, and promotes the intelligence of the safety procedures for power grid operations.